Creating a New Era for Global Civilization Development by Deepening Exchanges and Mutual Learning - Yuan, Li (Napredak, 2024)
The international landscape has undergone deep changes in the past years, whereas the noise in the public opinion gives rise to the notions such as superiority, collision of civilizations, conflict of cultures etc. However, in the east of the world, China in the new era explores ways of interaction between nations and civilizations with its unique cultural spirit enriched by the concept of Chinese modernization and Xi Jinping’s vision of the necessity of cooperation expansion among diverse civilizations. Committed to exchanges and integration of different civilizations and focusing on the high-quality Belt and Road cooperation, China vigorously advances the connectivity of people while at the same time building cooperation networks in, among other things, education, health, sports and tourism. China’s proposal for globalization in the post-pandemic era refrains from drawing ideological lines, not targeting a third party, nor striving for the formation of an exclusive bloc. Instead, China advocates respect of diversity and differences and works on building a community with the common future for whole humanity.